Pre-monsoon physico - chemical analysis of surface and ground water of Abhanpur block in district Raipur, (C.G.) - Sharma, Pramisha; Dubey, Amit; Chatterjee, S K (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> A segment of this investigation was carried out for pre-monsoon study of ground water as well as surface water physicochemical characteristics of Abhanpur block, district Raipur of Chhattisgarh. The geographical area at study is situated between 2103’N to 21035’4”N altitude and 81043’ E to 49.64’5” E longitude. The present work has been conducted by monitoring of ground and surface water i.e. well water and bore well water of 8 wards of Abhanpur Block as well as pond and tap water of the Abhanpur. Attempts were made to study and analyze the physico-chemical characteristics of water i.e. Temperature, pH, total dissolved solids, alkalinity, hardness and chloride. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->